A review of processing techniques for graphene-reinforced metal matrix composites - Naseer, Abqaat; Faiz, Ahmad; Aslam, Muhammad; Beh, Hoe Guan; Wan Sharuzi, Wan Harun; Norhamidi, Muhamad; Muhammad Rafi, Raza; German, Randall M. (Taylor & Francis, 2019)
In the quest to enhance reinforcement efficiency of graphene in metal matrices, various processing techniques have been devised over recent years. As the advancement in this field nowhere seems to slow down, the processing aspects of graphene-reinforced metal matrix composites are becoming more relevant than ever. In that premise, there lies an imminent need for a critical assessment of existing fabrication routes and their ability to extend a solution for the primary challenges of agglomeration, dispersion, interfacial interaction and structural integrity of graphene in metal matrix composites. This review presents a brief yet a meaningful insight to the processing techniques for graphene-reinforced metal matrix composites, while highlighting the key findings from individual studies, thereby expressing the primitive challenges and strengthens of these techniques. A critical evaluation of state of the art is presented alongside an inclusive review of improvement in mechanical, thermal, and electrical properties of composites fabricated by various processing routes. In the consideration of reviewed literature, it is established that a comprehensive processing strategy with a potential to simultaneously address all of the key processing challenges of graphene, is yet to nurture. Conclusively, future road map and a potential solution encompassing hybrid processing strategies, is opined.